2016
DOI: 10.1186/s41043-016-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of household wealth on child survival in Ghana

Abstract: BackgroundImproving child health is one of the major policy agendas for most of the governments, especially in the developing countries. These governments have been implementing various strategies such as improving healthcare financing, improving access to health, increasing educational level, and income level of the household to improve child health. Despite all these efforts, under-five and infant mortality rates remain high in many developing nations. Some previous studies examined how economic development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
10
34
2
Order By: Relevance
“…The results further indicated that children that were born as twins had lower probability of surviving across the different estimated models, when compared with single births. Similar results had been reported by Schoeps et al [69] and Lartey et al [70]. In the context of socio-economic conditions in Comoros, inadequate nutrition, inadequate healthcare facilities and persistent poverty can reduce survival of twin children.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results further indicated that children that were born as twins had lower probability of surviving across the different estimated models, when compared with single births. Similar results had been reported by Schoeps et al [69] and Lartey et al [70]. In the context of socio-economic conditions in Comoros, inadequate nutrition, inadequate healthcare facilities and persistent poverty can reduce survival of twin children.…”
Section: Discussionsupporting
confidence: 87%
“…In some other instances, immediate care by mothers to twin children may be delayed due to some complications accompany their birth [71,72,73]. Some other studies from Bangladesh [74], Nigeria [75], Ghana [70], and some countries in southern and eastern Africa [76] had reported similar findings.…”
Section: Discussionmentioning
confidence: 79%
“…The differential effect can be explained by the fact that children in rich households are likely have easy access to nutritious food and better caring practices, prerequisites for optimal child health. The effect of household wealth on normal Hb concentration could be a confirmation of the widely recognised health benefits of living in better-off households 44,[48][49][50] . Conversely, Agho and colleagues 51 observed that children from the richest and middle-class households had a lower Hb concentration than those from the poorest households 51 .…”
Section: Discussionmentioning
confidence: 81%
“…16 Low income is associated with higher rates of infant and under-five mortality similarly to our findings. [16][17][18] For instance, in Myanmar under-five children from the lowest wealth quintile household experienced a higher rate of death compared to their counterparts from the highest wealth quintiles. Poorer households are likely to account for a large proportion of the population living in rural and remote locations characterised by inadequate housing infrastructure.…”
Section: Discussionmentioning
confidence: 99%